Superior Pseudocapacitive Storage of a Novel Ni3Si2/NiOOH/Graphene Nanostructure for an All-Solid-State Supercapacitor - Ning, Jing; Xia, Maoyang; Wang, Dong; Feng, Xin; Zhou, Hong; Zhang, Jincheng; Hao, Yue (Nano-Micro Letters, 2020)
Recent developments in the synthesis of graphene-based structures focus on continuous improvement of porous nanostructures, doping of thin films, and mechanisms for the construction of three-dimensional architectures. Herein, we synthesize creeper-like Ni3Si2/NiOOH/graphene nanostructures via low-pressure all-solid melting-reconstruction chemical vapor deposition. In a carbon-rich atmosphere, high-energy atoms bombard the Ni and Si surface, and reduce the free energy in the thermodynamic equilibrium of solid Ni–Si particles, considerably catalyzing the growth of Ni–Si nanocrystals. By controlling the carbon source content, a Ni3Si2 single crystal with high crystallinity and good homogeneity is stably synthesized. Electrochemical measurements indicate that the nanostructures exhibit an ultrahigh specific capacity of 835.3 C g−1 (1193.28 F g−1) at 1 A g−1; when integrated as an all-solid-state supercapacitor, it provides a remarkable energy density as high as 25.9 Wh kg−1 at 750 W kg−1, which can be attributed to the free-standing Ni3Si2/graphene skeleton providing a large specific area and NiOOH inhibits insulation on the electrode surface in an alkaline solution, thereby accelerating the electron exchange rate. The growth of the high-performance composite nanostructure is simple and controllable, enabling the large-scale production and application of microenergy storage devices. Highlights: 1 Three types of Ni3Si2 were successfully fabricated by low-pressure all-solid melting-reconstruction chemical vapor deposition, and the growth pattern changed with the carbon source content. 2 In a carbon-rich atmosphere, high-energy atoms bombard the Ni and Si surface, and reduce the free energy in the solid Ni–Si particles’ thermodynamic equilibrium, considerably catalyzing the growth of Ni–Si nanocrystals. 3 Ni3Si2/NiOOH/graphene provides a large specific area and NiOOH inhibits insulation on the electrode surface in an alkaline solution and accelerates the electron exchange rate.